Frequency of Thyroid Carcinoma in Multi Nodular Goiter - Laraib Khan, Imran Khan, Ajmal Khan Jogezai, Sajjad Sarwar Magsi, Nourang Khan, Junaid Riaz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study was to determine the frequency of thyroid carcinoma in patients presenting with multinodular goiter in BMCH. Study Settings: Research was conducted at Department of General Surgery, Bolan Medical Complex Hospital Quetta. Material and Methods: Eighty four patients from both the genders with age between 20-75 years presenting with multinodular goiter since 3 months and meeting inclusion criteria were included in this study after taking informed written consent. All the thyroidectomies were done by consultant general surgeon of the hospital. Post-operatively all the patients were managed as per hospital protocol. Post thyroidectomy specimen was sent for histopathology for diagnosis of thyroid malignancy as per operational definition. All the other findings of study variables such as age, gender, place of residence, BMI (weight in Kg/Height in m2), family history of malignancy, diabetes, hypertension, smoking (>5 cigarettes/day for 2 years) and duration of goiter were noted in a predesigned proforma. Results: The mean age of the patients was 37.4±14.0 years. Majority (n=48, 57.1%) of the patients were aged between 25-50 years, followed by 23 (27.4%) patients aged <25 years and 13 (15.5%) patients aged >50 years. There were 17 (20.2%) male and 67 (79.8%) female patients with a male to female ratio of 1:4. Family history of thyroid malignancy was positive in 11 (13.1%) patients. Thyroid carcinoma was detected in 12 (14.3%) patients with multinodular goiter. When stratified, the frequency of thyroid carcinoma was significantly higher among smokers (29.2% vs. 8.3%; p-value=0.014) and those with positive family history of thyroid cancer (36.4% vs. 11.0%; p-value=0.047). However, no statistically significant difference was observed across various subgroups of patients based on age (p-value=0.978), gender (p-value=1.000), BMI (p-value=1.000), duration of goiter (p-value=0.928), place of residence (p-value=1.000), diabetes (p-value=0.928) and hypertension (p-value=0.858). Conclusion: In the present study, we observed that a substantial proportion of patients with multinodular goiter had concealed thyroid carcinoma particularly smokers and those with positive family history which warrants careful pre-operative evaluation of such patients for thyroid malignancy so that it may be identified well in time and appropriate management may be initiated to improve outcomes in future practice. Keywords: Multinodular Goiter, Thyroid Carcinoma, Positive Family History, Smoking